Assessment of ecological potentials using the MCDM Model to determine the optimal directions for industrial development in the Tabriz and Ardebil corridor - Khaliji, Mohammad Ali; Jafarpour Ghalehteimouri, Kamran (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2024)
Abstract Urban and regional development, along with industrial expansion, will expose extensive land areas to various human activities. Unfortunately, the ecological aspects of these developments have often been neglected, resulting in a lack of effective assessment tools to guide stakeholders towards sustainable land use practices that minimize negative impacts on the ecosystem. Utilizing land without considering its environmental potential and ecological diversity can have severe and irreversible consequences, including environmental degradation that threatens natural resources and hinders the environment's ability to support ongoing development. Inappropriate and poorly planned industrial growth can lead to the loss of agricultural land, environmental imbalances, and disruptions to ecological harmony. This study aims to determine the optimal location for industrial development in Ardebil. To achieve this objective, an optimization algorithm with an adaptive inertia weight based on Multiple Criteria Decision Making Models was employed. Key factors considered in the study include natural parameters (such as topography, slope, distance to fault lines), hydrological parameters (including land use, communication infrastructure), and energy-related factors (such as energy and drainage density). The findings reveal that geological criteria like soil quality and texture, as well as land use patterns, have the most significant impact on industrial development, with coefficients of 0.11 and 0.14, respectively. As a result, Parsabad, Sarein, and Ardebil are identified as the top three locations for industrial ecological development, while Khalkhal and Kosar are ranked ninth and tenth, respectively.